DeWS: Design skills through web stimuli - Raja Hussain, R.M.; Sinnappan, G.S. (2008)
Learning activities can be designed and developed to encourage students to actively engage in an open learning environment. The use of the Web as a tool to stimulate learning illustrates a paradigm shift in the teaching-learning process. Web-based stimulation is a process to encourage students to develop their skills in designing interface objects. DeWS (Design Skills through Web Stimuli) is a learning environment that encourages students to design interface objects using human-computer interaction (HCI) principles for user centered applications. This paper will present the findings of a DeWS pilot study on a group of 15 students in a Diploma in Computer Studies course in a private higher education institution. The study uses five techniques of guided learning with Web resources to stimulate the development of the design skills of five groups of first semester diploma students enrolled in the User-Interface Design module. Data were collected by means of observations and interviews. Students were given design tasks for completion within a certain time frame. Students were found to be able to produce appropriate design objects in the DeWS learning environment. Various learning outcomes related to designing skills were discovered when the web stimuli was used to engage the students in learning design skills.